Task implementation heterogeneity and wage dispersion - Stefano Visintin; Kea Tijdens; Stephanie Steinmetz; Pablo de Pedraza (IZA Journal of Labor Economics, 2015)
Wage dispersion among observationally similar workers is still only partially unexplained by economists from both a theoretical and an empirical point of view. Given that jobs can be broken down into tasks, namely units of work activities producing output, we empirically test whether part of the observed variation in wages across similar individuals is related to differences in the intensity with which tasks are implemented. We then investigate whether the variety in task implementation shown across occupations is related to cross-occupation wage levels. We found that the variation in task implementation in different occupations is related both to within-occupation wage dispersion and to cross-occupation wage levels: workers in high-wage occupations are less defined around a typical worker than those in other occupations.
Keywords: J22; J24; J31; 330; Tasks; Wages; Wage dispersion; Workers; Skills